2021
DOI: 10.1021/acssuschemeng.1c05408
|View full text |Cite
|
Sign up to set email alerts
|

Very High-Char-Yielding Elastomers Based on the Copolymers of a Catechol/Furfurylamine Benzoxazine and Polydimethylsiloxane Oligomers

Abstract: Main chain-type elastomeric polybenzoxazines (abbreviated as CA-pdms-fu) with very high char yield have been developed. Seven compositions of elastomeric benzoxazine adhesives are synthesized to find the optimum structure by changing the chain length of the siloxane component. The successful synthesis of CApdms-fu derived from catechol is confirmed with 1 H NMR and FT-IR spectroscopy. Polymerization characteristics, including polymerization temperature, enthalpy of polymerization, and extent of polymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 105 publications
0
14
0
Order By: Relevance
“…They found that the rubber-modified polybenzoxazine was able to protect carbon steel from corrosion. In 2021, Ishida et al 28 have reported the development of high-char-yielding elastomers based on polydimethylsiloxane oligomers functionalized with benzoxazine groups for adhesive applications.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the rubber-modified polybenzoxazine was able to protect carbon steel from corrosion. In 2021, Ishida et al 28 have reported the development of high-char-yielding elastomers based on polydimethylsiloxane oligomers functionalized with benzoxazine groups for adhesive applications.…”
Section: Introductionmentioning
confidence: 99%
“…Both degradation temperatures are considered quite high. The char yield, on the other hand, is very low for benzoxazines, particularly for those containing a CF 3 group, which is typically in the range of 36–68% [ 7 , 11 , 12 , 17 , 19 , 23 , 23 , 27 , 34 ], or a furan group, which is typically between 30–74% due to high crosslinking capabilities [ 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The char yield at 800 °C was approximately 24%, which is unexpectedly low for a benzoxazine such as BAF-oda-fu, which contains both above functionalities.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Attempts have been made to decrease chain mobility of BZ resin to improve its thermal and mechanical properties by incorporating unsaturated (such as allyl or alkynyl) groups, blending with high-performance polymers to form miscible blends, [10][11][12][13][14][15][16] and adding inorganic nanoparticles. [17][18][19][20][21][22] Many organic/inorganic polybenzoxazine (PBZ) hybrids (and other thermosetting resins) have been prepared by incorporating carbon-based materials (e.g., carbon nanotubes, [23][24][25] carbon black, [26] and graphene [27][28][29][30] ) and siliconbased materials [e.g., polydimethylsiloxane (PDMS), [5,[31][32][33] organic modified clay, [34,35] and polyhedral oligomeric silsesquioxane (POSS) [17][18][19][20][21][22][36][37][38][39][40] ]. For example, polymer/POSS hybrids have been obtained from mono-and multifunctionalized POSS derivatives through blending or copolymerization, initially forming organic/inorganic hybrids with only relatively lowmolecular-weight or insoluble cross-linked structures.…”
Section: Introductionmentioning
confidence: 99%